If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = hx + f Reorder the terms: y = f + hx Solving y = f + hx Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = f + hx
| 3x^3+14x^2-12x=0 | | 9c+5-6=9 | | 5x^3-3x-2=0 | | 16x=12x+52 | | X-1=2y | | a^3b^5x=a^7b^5c^3 | | 3y^5*6y= | | 12x(x+1)=42(x+1)-(3x-42) | | 4.5=-3(-2.5)+b | | 2n-14=-8(7+5n) | | 2n-1=-8(7+5n) | | 3.14r^2=5 | | 3(3.5x+3.75)=3(4.75x+4) | | 6x-2=3x-44 | | 9e-5=22 | | 6x-1=2x-93 | | 25X^2+8X=0 | | 60=5x-5 | | 7(4x-9)+10=5x-5 | | 9x-4=75 | | -15x=1479 | | 9-7x=209-42x | | 3x+30=3 | | -3x+6x^2+5x+9x= | | 300-3P=3P | | 3+7(w+7)+w= | | 11x-3x=14 | | 37=5c-8 | | 11x+7+10x=31 | | 3x^2+5x=-4 | | 12x+24=28x-8 | | -34-4x=4x+22 |